2021
DOI: 10.1111/jfpp.15658
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of drying temperature for the assessment of functional and physical characteristics of autumn olive berries

Abstract: Autumn olive (Elaeagnus umbellata Thunb) is an ornamental plant belonging to Elaeagnacea family and widely found in Southern Europe, Central Asia, and Americas (Ishaq et al., 2015;Wang et al., 2007). It is a vigorous shrub of 3.5 to 5.5 m height and 3.5 to 5.5 m width having tolerance of poor soil, drought and disease due to its ability to fix nitrogen (Ishaq et al., 2015;Wu et al., 2011). Autumn olive produces small deep-red colored sweet-tart and is planted to prevent erosion and provide screening along path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 61 publications
4
17
0
Order By: Relevance
“…First, some physicochemical properties of fresh autumn olive berries were shown in Table 1. The obtained results were very close to our previous studies and others in the literature [3,[5][6][7]29,30]. These small red berries are a rich source of lycopene and have a high-water content.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…First, some physicochemical properties of fresh autumn olive berries were shown in Table 1. The obtained results were very close to our previous studies and others in the literature [3,[5][6][7]29,30]. These small red berries are a rich source of lycopene and have a high-water content.…”
Section: Resultssupporting
confidence: 91%
“…Autumn berries are widely thought to protect human health from several diseases and some cancers (e.g., prostate cancer). These sweet-tart berries can be consumed fresh or used for preserves, fruit rolls, juice, and other food products [3,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…drying process could perturb the cell wall and release antioxidant compounds, thus increasing the supply of bio-accessible antioxidant compounds(Choi, Lee, Chun, Lee, & Lee, 2006;Zannou, Pashazadeh, Ghellam, Hassan, & Koca, 2021).The ABTs and DPPH inhibition percentages for coriander dried in microwaves at 100, 500, and 1,000 W are 44.99, 81.84, and 83.33%for ABTs and 61.21, 70.06, and 71.94% for DPPH, respectively. The percentages increase as the power increases, a result consistent with that obtained byHamrouni-Sellami et al (2012), who found that, as the microwave drying power increases from 600 to 800 W, the antioxidant activity of sage increases.…”
mentioning
confidence: 99%
“…Design-Expert 8.0.7.1 software was used to do quadratic polynomial regression analysis toward the results in Table 3 to obtain the following eight ternary quadratic regression equations: However, the closeness of R 2 and adjusted R 2 confirmed the experimental conformity, predicted data, and the present model could be usedtopredict the design space (Zannou et al, 2021). The coefficients of variation (CV) were between 2.31%-16.25%, and since the smaller the coefficient of variation, the higher the confidence, this indicated that the obtained model had high confidence in the stipe chewiness (Y 6 ) and extremely high confidence in other response values (Singh et al, 2021).…”
Section: Establishment and Variance Analysis Of Regression Equationmentioning
confidence: 87%